2008
DOI: 10.1126/science.1161437
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Perseverative Search Errors Are Induced by Pragmatic Misinterpretation

Abstract: Having repeatedly retrieved an object from a location, human infants tend to search the same place even when they observe the object being hidden at another location. This perseverative error is usually explained by infants' inability to inhibit a previously rewarded search response or to recall the new location. We show that the tendency to commit this error is substantially reduced (from 81 to 41%) when the object is hidden in front of 10-month-old infants without the experimenter using the communicative cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(152 citation statements)
references
References 19 publications
9
141
0
2
Order By: Relevance
“…Even the most conscientious confederates are at risk of inadvertently shaping participants' behavior by giving verbal backchannels or nonverbal cues such as facial expressions, body posture, tone of voice, pauses, or eye gaze patterns. Research has shown that these types of cues from an experimenter or examiner can influence people to do better on IQ tests (Congdon & Schober, 2002), inspire children to excel in their schoolwork (Rosenthal & Jacobson, 1968, lead infants to discard principles of object permanence (Topál, Gergely, Miklósi, Erdöhegyi, & Csibra, 2008), and even cause horses to behave as if they can read and do math (Pfungst, 1907).…”
Section: Concerns Risks and Findingsmentioning
confidence: 99%
“…Even the most conscientious confederates are at risk of inadvertently shaping participants' behavior by giving verbal backchannels or nonverbal cues such as facial expressions, body posture, tone of voice, pauses, or eye gaze patterns. Research has shown that these types of cues from an experimenter or examiner can influence people to do better on IQ tests (Congdon & Schober, 2002), inspire children to excel in their schoolwork (Rosenthal & Jacobson, 1968, lead infants to discard principles of object permanence (Topál, Gergely, Miklósi, Erdöhegyi, & Csibra, 2008), and even cause horses to behave as if they can read and do math (Pfungst, 1907).…”
Section: Concerns Risks and Findingsmentioning
confidence: 99%
“…Dogs in the Non-Social UMO treatment condition did not commit the A-not-B error, since their performance did not decrease significantly from A to B trials [3], as predicted if they did not consider the 'beep' cues conveyed by the UMO as having relevance. They responded similarly to dogs with a non-communicative human, or no partner (ball moved by 'invisible' string) in previous work [4].…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestive link between this finding and a recent attempt to explain the A not B search error. Topál, Gergely, Mikló si, Erdõ hegzi, and Csibra (2008) demonstrated that infants were more likely to make the error if the hider engaged them in eye contact and interaction. Their conclusion is that the error results from a misinterpretation of the adult's social cues, a misinterpretation in the sense that they take socially marked hiding at A to indicate that this is the place to search for objects.…”
Section: Perception Of Goal-directed Action and Animacymentioning
confidence: 99%